2003
DOI: 10.1115/1.1582501
|View full text |Cite
|
Sign up to set email alerts
|

Target Cascading in Optimal System Design

Abstract: Target cascading is a key challenge in the early product development stages of large complex artifacts: how to propagate the desirable top level design specifications (or targets) to appropriate specifications for the various subsystems and components in a consistent and efficient manner. Consistency means that all parts of the designed system should work well together, while efficiency means that the process itself should avoid iterations at later stages, which are costly in time and resources. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
279
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 443 publications
(280 citation statements)
references
References 12 publications
1
279
0
Order By: Relevance
“…The analytical target cascading (ATC) formulation is another example in this category, but now formulated for an arbitrary number of levels (Michelena et al 1999;Kim 2001;Kokkolaras et al 2002;Kim et al 2003;Michelena et al 2003). Various penalty functions φ j have been proposed for ATC (see Michelena et al 2003;Kim et al 2006;Tosserams et al 2006), and a comparison can be found in Li et al (2008).…”
Section: Closed Design Open Consistencymentioning
confidence: 99%
“…The analytical target cascading (ATC) formulation is another example in this category, but now formulated for an arbitrary number of levels (Michelena et al 1999;Kim 2001;Kokkolaras et al 2002;Kim et al 2003;Michelena et al 2003). Various penalty functions φ j have been proposed for ATC (see Michelena et al 2003;Kim et al 2006;Tosserams et al 2006), and a comparison can be found in Li et al (2008).…”
Section: Closed Design Open Consistencymentioning
confidence: 99%
“…Other common relaxation formulations involve penalty functions 39 or an augmented Lagrangian 10 function. Each decomposition formulation can be subdivided into:…”
Section: Iiia Physical Couplingmentioning
confidence: 99%
“…Sobieszczanski-Sobieski et al (1987), 76 Alexandrov and Dennis (1994), 1 Kim et al (2003), 41 amongst others) and multi-disciplinary optimization (e.g. Braun and Kroo (1997), 22 Rodriguez et al (2000), 57 Sobieszczanski-Sobieski et al (2000), 71,72 amongst others) techniques have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…This technique then attempts to minimize deviations between design targets and subsystem responses to achieve an optimal solution for the system [21,22].…”
Section: Review Of Analytical Target Cascadingmentioning
confidence: 99%